Improving Responsiveness of Supply Chain for a Customized Product, A Case Study at a Swedish Lighting Company - SKULVILAILERT, ARPAPAT; BABAABADI, NEDA (My University, 2016)
Globalization has made international sourcing as one of the most interesting issues in many literatures and organizations. Moreover, supply chain area is facing new challenge known as customized production, which forces the companies to manage the rapid change and uncertain demand in order to be competitive in the market. In this thesis, a case study was performed at a lighting company in Gothenburg. The study focuses on one customized mechanical component which has very long lead time and high transportation cost. The purpose of the study is to study the whole supply chain of the component from the Chinese suppliers to the lighting company in Sweden in order to provide recommendations for adaptations that could increase responsiveness of the supply chain. Information provided by the lighting company, the logistics company and the Chinese supplier were used for analysis. The extended value stream map was used to identify the problems in material and information flows of the mechanical component. Transportation costs were calculated and compared for using the sea and rail transportation modes. The analysis has shown that there are many supply chain issues which could be improved along the whole supply chain of the mechanical component. The future state map was created to illustrate adaptations which will shorten the lead time and reduce transportation costs. Short and long term plans for implementing the changes regarding to the future state map are presented in this thesis. In order to increase responsiveness in the material flow, an appropriate level of safety stock in the lighting company, the Chinese supplier and the subcontractor company have been recommended. Furthermore, two material planning provided in this thesis are alternative choice in order to prevent out-of-stock at the lighting company. Effective information sharing and new supply contract conditions between parties involved in the supply chain, have also been suggested for improving responsiveness of the supply chain for mechanical components.
Keywords: Samhällsbyggnadsteknik; Civil Engineering